1985
DOI: 10.1111/j.1365-2265.1985.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of Goitre in Epileptic Patients on Long‐term Phenytoin or Carbamazepine Treatment

Abstract: Thyroid function, the clinical occurrence of goitre and ultrasonically determined thyroid gland volume were investigated in 23 patients with phenytoin- and 28 patients with carbamazepine-treated convulsive disorders and compared with matched healthy controls. In the phenytoin treated group median thyroid volume was 26 ml (range 14-57 ml) compared to 17 ml (range 8-41 ml) in the controls (P less than 0.01). Ten patients and four controls had a goitre (NS). Median serum T4 and FT4I levels were reduced, serum TSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In humans, chronic treatment with PB-like inducer phenytoin is also reported to decrease levels of total serum T4, promoting thyroid hypertrophy (Hegedus et al, 1985, Curran and DeGroot, 1991. However, it is not known whether this decrease is caused by the augmentation of metabolism and/or excretion of TH or the attenuation of TH synthesis.…”
Section: S Kodama and M Negishimentioning
confidence: 96%
“…In humans, chronic treatment with PB-like inducer phenytoin is also reported to decrease levels of total serum T4, promoting thyroid hypertrophy (Hegedus et al, 1985, Curran and DeGroot, 1991. However, it is not known whether this decrease is caused by the augmentation of metabolism and/or excretion of TH or the attenuation of TH synthesis.…”
Section: S Kodama and M Negishimentioning
confidence: 96%
“…The higher frequency of patients with thyroid enlargement were on combined therapy (CBZ + VPA) (45%) followed by those on VPA (30%). Previous studies reported thyroid enlargement with enzyme-inducing and non-enzyme inducing AEDs (5,29,40). Hegedüs et al (5) reported increased thyroid volume with CBZ (range: 13-66 ml, mean: 25 ml; versus range: 9-44 ml, mean: 16 ml for controls; p<0.010).…”
Section: Neurology and Neuroscience Issn: 2386-687xmentioning
confidence: 99%
“…Some studies reported ultrsongraphic evidence of thyroid enlargement (goiter). Also, these studies reported significant correlation between thyroid volume and thyroid hormonal abnormalities (5,29).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the chronic elevation in TSH secretion documented in both rodents and humans receiving such compounds causes thyroid malignancies in rodents, whereas only thyroid enlargement has been observed in humans (22)(23)(24)(25). In patients without the capacity for internal compensation, such as those with hypothyroidism, the xenobiotic-induced increase in the rate of hormone metabolism will increase the replacement dosage requirement that can be critically important to fetal development during pregnancy.…”
mentioning
confidence: 99%
“…A increase in TSH would compensate for this by accelerating T 4 and T 3 secretion. The sustained TSH-driven increase in the rate of thyroid follicular cell division can lead to thyroid malignancies in rodents, although not in humans (22)(23)(24)(25). Despite this increased stress upon the thyroid, hypothyroidism should not occur as long as the hypothalamicpituitary thyroid axis is intact and iodine supplies are sufficient.…”
mentioning
confidence: 99%